DRUG UTILIZATION EVALUATION OF ANTIDIABETIC DRUGS AMONG TYPE 2 DIABETES PATIENTS OF TAMIL NADU - P, Geetha; P, Shanmugasundharam (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The aim of the study was to assess the prescribing pattern of antidiabetic drugs in Type 2 diabetes outpatients visiting to Diabetes Centre, Chennai. Methods: A prospective study was carried out by evaluating 115 prescriptions of antidiabetic drugs over the period of 4 months to assess the prescribing pattern of antidiabetic drugs and also drugs used for other complications of Type 2 DM. Results: Totally, 115 patients were evaluated, 58 were of male and 57 were of female. An average number of drugs per encounter were found to be 4.47. An average number of antidiabetic drugs were found to be 2.56. In this study, the most commonly prescribed oral hypoglycemic drug class as single-drug regimen was that of alpha-glucosidase inhibitors (16.326%), dipeptidyl peptidase-4 (DPP-4) inhibitors (14.62%), biquanides (12.9%), thiazolidine diones (9.8%), sulfonyl urea (7.82%) and meglitinides (2.38%), and in multi drug regimen metformin + alpha-glucosidase inhibitors (11.56%) were commonly prescribed. Conclusion: Most commonly used drug was alpha-glucosidase inhibitors, followed by DPP-4 inhibitors and biguanides. All the patients received combination therapy to achieve the glycemic control.